“That’s Not Rehabilitation, That’s Enabling”: Correctional Officer Perspectives on the Prison Needle Exchange Program - Johnston, Matthew S. (Criminal justice and behavior, 2024)
Correctional Service Canada implemented Prison Needle Exchange Programs (PNEPs) into federal penitentiaries in 2018 as a harm reduction measure to prevent needle sharing, drug overdose, and limit the spread of infectious disease. However, studies demonstrate how staff resistance hinders the growth of these programs within Canadian prisons. Drawing on interview data produced by 134 federally employed and relatively new correctional officers in Canada, the current study analyzes officers’ levels of support and (more often) opposition to PNEP. Results indicate that, predominantly, staff opposition to PNEP is rooted in safety concerns, a perceived lack of evidence of PNEP’s benefits, and fears the program is not promoting recovery and rehabilitation. By increasing the prevalence of needles in cells, officers report concern of overdose or potential weaponization of needles. Our study informs policy discussions around harm reduction measures in prisons to better promote institutional safety, public health, and nonstigmatized approaches to substance use.